Disparities in cancer survival and incidence by metropolitan versus rural residence in Utah. (13th March 2018) - Hashibe, Mia; Kirchhoff, Anne C.; Kepka, Deanna; Kim, Jaewhan; Millar, Morgan; Sweeney, Carol; Herget, Kimberley; Monroe, Marcus; Henry, N. Lynn; Lopez, Ana‐Maria; Mooney, Kathi
Abstract: Cancer disparities in rural and frontier communities are an important issue in Utah because much of Utah is sparsely populated. The aims of this study were to investigate whether there are differences in the cancer incidence and 5‐year survival rates in Utah by metropolitan/rural residence and to investigate disparities in distributions of cancer risk factors. We used cancer registry records to identify patients diagnosed with a first primary cancer in Utah between 2004 and 2008. We estimated 5‐year survival and incidence rates. The Cox proportional hazards model was used to estimate hazard ratios (HRs) for the risk of death. There were 32, 498 (86.9%) patients with cancer who lived in metropolitan counties and 4906 (13.1%) patients with cancer who lived in rural counties at the time of cancer diagnosis. Patients with cancer from rural counties were more likely to be older, American Indian/Alaskan Native, non‐Hispanic, male, and diagnosed at higher stage. Rural residents had a five‐year relative survival that was 5.2% lower than metropolitan residents and a 10% increase in risk of death (HR = 1.10, 95% CI = 1.03, 1.18) after adjustment for multiple factors. Overall, the cancer incidence rates in rural counties were lower by 11.9 per 100, 000 per year (449.2 in rural counties vs. 461.1 in metropolitan counties). Cancer patients living in rural counties of Utah had different demographic characteristics as well as differences in incidence and survival rates. Further studies with individual‐level data are necessary to investigate the reasons behind these differences in cancer incidence and survival to reduce disparities. Abstract : Cancer disparities in rural and frontier communities are an important issue in Utah because much of Utah is sparsely populated. Patients with cancer from rural counties in Utah were more likely to be older, American Indian/Alaskan Native, non‐Hispanic, male, and diagnosed at higher stage. Rural residents had a five‐year relative survival that was 5.2% lower than metropolitan residents and a 10% increase in risk of death (HR = 1.10, 95% CI = 1.03, 1.18) after adjustment for multiple factors.